Developing Mathematic Learning Devices Oriented Problem Based Learning to improve Students' High Order Thinking Skill - Qohar, Moh. Abdul; Susanti, Nawal Ika; Wahyu, Rahma (Universitas Islam Negeri Sunan Kudus, 2025)
Students demonstrate low proficiency in answering HOTS (Higher Order Thinking Skills) questions, indicating the need for a learning model that aligns with the nature and demands of such questions. One such suitable model is Problem-Based Learning (PBL), which serves as a relevant and applicable approach for the current curriculum. This study aims to develop a mathematics learning tool based on the Problem-Based Learning (PBL) model to enhance students’ higher-order thinking skills (HOTS). This research employed the 4D Model in the research and development (R&D) approach, encompassing the stage of define, design, develop, and dissemination. The sampling used a purposive sampling technique, namely 22 students of SMP Plus Darussalam Blokagung Banyuwangi. The expert validation results showed that the lesson plan (RPP) achieved an average score of 92.2%, placing it in the